Welfare Becomes Punishment: Penal Nationalism in Danish Social Policy - Bjerre, Cecilie (The British journal of criminology, 2025)
In this article, we demonstrate how ‘penal nationalism’ came to influence Danish social policy during the 2000s. While critical evaluations of the Nordic Exceptionalism thesis have underscored the significance of immigration in shaping both penal and border policies of the Nordic welfare states, our analysis delves into the core of the Danish welfare state by examining the implementation of the social policy tool, Parenting and Youth Orders. Through this case study, we show how penal instruments were integrated into social policy to regulate citizens with immigrant backgrounds residing in Denmark. These political innovations encompass the reinforcement and legitimization of (1) the explicit targeting of citizens with ethnic minority background and (2) the utilization of new penal instruments within the social realm.